CONTROLLING GREED THROUGH INNER ENGINEERING- FEW TIPS FOR FINANCE PROS. - Professor Shirish Raibagkar (International Journal of Research Science and Management, 2014)
Imagine you are in the boxing ring waiting for your opponent. And the announcement says that you are your opponent! When we fight greed, whom are we fighting against? Is greed YOU or is it something different than YOU? If one has to fight with someone or something that someone or something should have a separate existence in the first place. Is OUR greed really OURS? If you are interested to beat YOUR greed, then read on and discover an innovative technique of controlling greed called the “Science of Separation”.